Proposta de um manual para captar recursos à cultura pelo viés do incentivo fiscal da dedução no IRPF dos servidores da Universidade Federal de Santa Maria - Pereira, Suziane Deyse Vaz (2017)
The economic advance of a country results from the human progress of its people, that is, from a cultural refinement that magnifies people, making them more critical and knowledgeable. However, awareness of the importance of culture, of the need to direct resources to the continuity of cultural actions and of volunteering the contribution to the cultural area, rarely arise without an equivalent stimulus from the State. In Brazil, this is no different, since, historically, the main support to culture has always been government support. However, the raising of funds through other sources of financing was accentuated when the State left room for investments in the area with the creation in 1991 of Law 8,313, the so-called Culture Incentive Law or Rouanet Law, which established the National Program of Support to Culture and proposed the permission to individuals and legal entities to obtain deductions in Personal Income Tax (PIT) related to donations and / or sponsorship of cultural projects previously registered and approved by the Ministry of Culture (MINC). The present study aimed to propose the creation of a demonstration manual on fundraising for culture due to the incentive by the means of the Personal Income Tax deduction of the employees of the Federal University of Santa Maria (UFSM). For that, an applied scientific research, of exploratory nature, with qualitative approach was carried out. The data collection took place in November / 2016 and the choice of the UFSM servants was due to the fact that they have positions that belong to a Federal Career Plan, with income that leads many to retention of Withholding Tax (WHT) and subsequent PIT payment; which makes them possible source of contribution to cultural institutions based on the Rouanet Law. The elaboration of this work brought many considerations, both for the academic environment, through suggestions for future work, and for those servants of the UFSM, and, why not, the other individuals, who have an interest in directing part of their Personal Income Tax to contribute to the culture, through the indication of the indispensable procedures, particularities and obligatoriness that must be observed, in order to guarantee the effective contribution to the cultural institutions and projects that allow the subsequent deduction in the PIT. This all demonstrates an opportunity to encourage the legal channeling of part of the PIT due to generated in the Income Tax Return (ITR) to the cultural sector, and to promote the understanding of all about the application of the Rouanet Law in the Personal Income Tax.